IMF Staff papers : Volume 42 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1995)
This paper develops an endogenous growth model of the influence of public investment, public transfers, and distortionary taxation on the rate of economic growth. The growth-enhancing effects of investment in public capital and transfer payments are modeled, as is the growth-inhibiting influence of the levying of distortionary taxes that are used to fund such expenditure. The theoretical implications of the model are then tested with data from 23 developed countries between 1971 and 1988, and time series cross sectional results are obtained that support the proposed influence of the public finance variables on economic growth.